2021
DOI: 10.29309/tpmj/2021.28.04.4463
|View full text |Cite
|
Sign up to set email alerts
|

Association of nephrolithiasis with the intake of carbonated drinks.

Abstract: Objective: To determine the association between the consumption of carbonated drinks and development of kidney stones. Study Design: Matched Case-control study. Setting: Liaquat National Hospital Karachi, Pakistan. Period: June 2017 to December 2017. Material & Methods: We recruited patients of nephrolithiasis admitted in Nephrology ward at Liaquat National Hospital as cases and controls from General Surgery ward. The sample size calculated was 186, with 93 cases and 93 controls, matched for age. Descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…These come in agreement with Ferraro et al (2020), in Italy, showed higher risk for incident kidney stones for the consumption of one or more soda drinks per day compared with less than one per week. In contrast, Adeel et al (2021), in Pkistan, unable to find significant associations between intakes of carbonated drinks and kidney stones.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These come in agreement with Ferraro et al (2020), in Italy, showed higher risk for incident kidney stones for the consumption of one or more soda drinks per day compared with less than one per week. In contrast, Adeel et al (2021), in Pkistan, unable to find significant associations between intakes of carbonated drinks and kidney stones.…”
Section: Discussionmentioning
confidence: 74%
“…In disagreement with these results Esnaasharan et al (2020), in Iran, andAdeel et al (2021), in Pakistan, found that, no association between the volume of total fluid intake, and risk of kidney stones. However, according to Jafari et al ( 2019), wrong time of drinking water, such as during or immediately before, and after meals, may disturb food digestion, and increase ghaliz humor; therefore, liquid consumption should be limited to 20 minutes before and two hours after meals.…”
Section: Discussionmentioning
confidence: 87%